Influência da velocidade da soldagem TIG autógena sobre características macro e microestruturais e dureza de chapas finas de aço inoxidável duplex - Ferreira, Arthur José de Andrade (2024)
The present study aimed to evaluate the effects of TIG welding travel speed on thin sheets of duplex stainless steel UNS S32205, with a thickness of 2.3 mm, on the microstructure and hardness of the weld. Four weld joints were formed using the autogenous TIG welding process, under restraint, with a current of 100 A in direct polarity, maintaining constant flows of pure argon and varying travel speeds ranging from 36.3 to 64.6 mm · min-1. The autogenous welds were evaluated through visual inspection, measurement of angular distortion, optical microscopy and microhardness testing. The results of visual inspection showed an inverse relationship between travel speed and the extent of the heat-affected zone, except when the welding torch approached the workpieces. It was also observed that the welded samples exhibited distortions ranging from approximately 0.5 to 1.3°, associated with both length of the autogenous weld and its symmetry with the T-joint. Micrographic analysis revealed the presence of chromium clouds in ferrite grains in the heat-affected zone and in the fusion zone, as well as an imbalance in the ferrite and austenite phases due to the lack of nitrogen replenishment by the shielding gas. It was observed that travel speed is directly proportional to the austenite content and its structures, which directly influences the final microstructure, and indirectly related to the precipitate content and refinement of ferrite grain, causing the displacement of the maximum hardness value from the fusion zone to the heat-affected zone, depending on ferritic grain size, on phase imbalance favorable to ferrite, and on the chromium nitride precipitate content along the heat-affected zone.